The process of formation of communicative-speaking competence of social workers based on the system-target approach - Berezovska, Liudmyla (ScienceRise: Pedagogical Education, 2019)
The article deals with theoretical analysis of the literature on determining the place and role of the system-target approach in the process of formation of the communicative-speaking competence of future social workers in higher education institutions. It is indicated, that the usage of a system-target approach is aimed at forming in students a system of interdisciplinary knowledge from linguistic disciplines, communicative skills and skillful usage of them in future professional activities. The program of the elective course "Technologies of professional communication" was developed. The informative content of which predicted creation of a system of theoretical and methodological knowledge in students about the essence of communicative-speaking activity; the development of skills of professional-speaking communication; performance of practical tasks; communicative exercises (trainings); value attitudes; communicatively significant personal qualities; professional motives, interests, interpersonal interactions. The selection of exercises and tasks was carried out according to the following criteria: purpose; sequence and technique of the intended actions; self-control over the course and results of actions; control over the implementation of exercises and its results from the teacher. Exercise was aimed at practical mastering of the procedure and "technology" of communication on the basis of working out its most important elements, which promoted the development of communicative-speaking skills, acquisition of skills of management in the communication process, ensured the formation of organic and consistent actions in the public environment, technology and speech logic, its expressiveness and emotionality. Among the conditions that will ensure the effectiveness of educational activities at each stages of the communicative-speaking competence formation there were chosen: the creation of educational communication environment on the basis of a structural and target approach, oriented on compliance with the algorithm of action (analysis, planning, designing); realization of interdisciplinary connections of cycles of psychological and pedagogical, fundamental and professionally oriented disciplines; creating a supportive environment for communication, based on a human, tolerant attitude towards the interlocutor